Strong and ductile age-hardening Mg-Al-Ca-Mn alloy that can be extruded as fast as aluminum alloys. (15th May 2017) - Nakata, T.; Xu, C.; Ajima, R.; Shimizu, K.; Hanaki, S.; Sasaki, T.T.; Ma, L.; Hono, K.; Kamado, S.
Abstract: We have developed a wrought magnesium alloy, Mg-1.3Al-0.3Ca-0.4Mn (wt.%) or AXM10304, that can be extruded at a very high die-exist speed of 24 m/min, comparable to the extrusion speed for aluminum alloys, and that exhibits an excellent combination of strength and elongation after an age-hardening, i.e., a tensile 0.2% proof stress of 287 MPa and an elongation of 20%. The high tensile proof stress is attributed to the dispersion of a high number density of monolayer Guinier Preston (G.P.) zones dispersed in grains with an average grain size of 17 μm and <10 1 ¯ 0> fiber texture typical of Mg alloy extrusions. The uniform dispersion of the G.P. zones facilitates cross-slip, and the G.P. zones do not work as crack initiation and propagation site, so the degradation of the elongation after the age-hardening is prevented. The combination of strength and elongation of the extruded and age-hardened AXM10304 is superior to those of Mg-6Al-1Zn (AZ61) and Mg-6.0Zn-0.5Zr (ZK60) commercial alloys and comparable to those of 6000 series of aluminum alloys without any expensive ingredients. Therefore, this alloy may open up a new application areas where weight reduction is of a priority issue. Graphical abstract: Image